PERAN GREEN MARKET ORIENTATION, GREEN ENTREPRENEURIAL ORIENTATION, DAN GREEN SUPPLY CHAIN MANAGEMENT TERHADAP ENVIRONMENTAL PERFORMANCE - Khariq, Muhammad Taufan; Yunies Edward, Mohammad (Unitri Press, 2025)
The study aims examine the role of green market orientation, green entrepreneurial orientation, and green supply chain mamnagement on environmental performance. The research conducted used in quantitative with questionnaire instrument. Study uses quantitative data types. the data source in this study is primary. The primary data of this study will use a questionnaire that will be filled out by the manager of SMEs dijepara. The population in this study were SMEs in Jepara, using the slovin method with an alpha of 10%, the minimum number sample 97 respondents. Sampling technique is done use one of the non probability sampling methods. The results green entrepreneurial orientation has a positive effect on environmental performance, green market orientation and green supply chain management have no effect on environmental performance.